2007
DOI: 10.1016/j.ceb.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction channel structure in the early 21st century: facts and fantasies

Abstract: Gap junction channels connect the cytoplasms of adjacent cells through the end-to-end docking of single-membrane structures called connexons, formed by a ring of six connexin monomers. Each monomer contains 4 transmembrane α-helices, for a total of 24 α-helices in a connexon. The fundamental structure of the connexon pore is probably similar in unpaired connexons and junctional channels, and for channels formed by different connexin isoforms. Nevertheless, variability in results from structurally-focused mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 52 publications
0
87
0
2
Order By: Relevance
“…Consistent with changes in Cx43 folding that can accompany transport along the secretory pathway, conformation specific antibodies against the C terminus of Cx43 have been identified that specifically recognize either Golgi-or gap junction-localized Cx43 (Sosinsky et al, 2007). In particular, the fully formed connexin channel contains an aqueous pore lined by polar and charged amino acids from multiple connexin transmembrane domains (Yeager and Harris, 2007). Thus, the conformation Cx43 assumes when assembled into a hexamer is expected to be unstable for monomeric Cx43 because these polar residues would be exposed to the hydrophobic portion of the membrane instead of part of the aqueous pore.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with changes in Cx43 folding that can accompany transport along the secretory pathway, conformation specific antibodies against the C terminus of Cx43 have been identified that specifically recognize either Golgi-or gap junction-localized Cx43 (Sosinsky et al, 2007). In particular, the fully formed connexin channel contains an aqueous pore lined by polar and charged amino acids from multiple connexin transmembrane domains (Yeager and Harris, 2007). Thus, the conformation Cx43 assumes when assembled into a hexamer is expected to be unstable for monomeric Cx43 because these polar residues would be exposed to the hydrophobic portion of the membrane instead of part of the aqueous pore.…”
Section: Discussionmentioning
confidence: 88%
“…See Schneider and Simons [24] and van der Pol et al [25] for further information on extracellularvesicle-mediated intercellular communication. pathway for electrical and metabolic signalling between cells, especially astrocytes [40][41][42]. Usually, different astrocytes are coupled through GJs to form large intercellular networks [43,44].…”
Section: (B) Gap Junctionsmentioning
confidence: 99%
“…Three innexinrelated proteins, called pannexins, have persisted in vertebrates, although it is not clear if they form intercellular channels (Panchin et al 2000;Bruzzone et al 2003). 7Å -resolution electron crystallographic structures of intercellular channels composed of either a carboxyterminal truncation of Cx43 (Unger et al 1999;Yeager and Harris 2007) or an M34A mutant of Cx26 (Oshima et al 2007) are available. The overall pore morphologies are similar with the exception of a "plug" in the Cx26 channel pore.…”
mentioning
confidence: 99%